2017
DOI: 10.7196/samj.2017.v107i11.12577
|View full text |Cite
|
Sign up to set email alerts
|

Extraspinal osteoarticular multidrug-resistant tuberculosis in children: A case series

Abstract: These findings indicate that ESOA MDR-TB is a reality in this paediatric population (10.5%) and a high index of suspicion should be maintained, especially when cultures are negative in children with signs and symptoms of ESOA TB. The effect of HIV infection on the incidence of ESOA MDR-TB requires further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
1
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
1
0
2
Order By: Relevance
“…In a study examining extra-axial MSK TB in children, Firth et al reported a prevalence of 33.3% of HIV co-infection. 18 The reason for the low HIV co-infection rate in our patients remains elusive, but TB is endemic in our region, as is demonstrated by the four-times higher number of cases in our study than in that by Firth et al 18 over the same time period, and may be ascribed to different epidemiology and disease trends in our population.…”
Section: Discussionmentioning
confidence: 46%
“…In a study examining extra-axial MSK TB in children, Firth et al reported a prevalence of 33.3% of HIV co-infection. 18 The reason for the low HIV co-infection rate in our patients remains elusive, but TB is endemic in our region, as is demonstrated by the four-times higher number of cases in our study than in that by Firth et al 18 over the same time period, and may be ascribed to different epidemiology and disease trends in our population.…”
Section: Discussionmentioning
confidence: 46%
“…Consistently low study samples were reported by Firth et al (also from our Institution) looking at extra-spinal osteoarticular TB in 19 paediatric cases over a 16 years year period. 9 Our study had one paediatric case out of 34 cases over 5 years. Studies with large sample sizes over a short duration were reported in China and Thailand with 43 and 99 osteoarticular TB cases recorded in just two years respectively, this is possibly due to a large population and ailing sanitation measures, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The most important aspect of the treatment is choosing the correct course of anti-tubercular drugs due to the massive arising issue of multi-drug resistant tuberculosis, which is defined as MTB that is resistant to both isoniazid and rifampicin, regardless of other susceptibilities. 12 , 13 One of the recommended treatment regimens for OA-TB is a minimum of 3 drugs, including isoniazid, rifampin, pyrazinamide, and streptomycin or ethambutol, to which MTB is susceptible, and at least one of these drugs must be bactericidal. 13 Other studies recommend a therapy with 4 drugs, since the frequency of isoniazid resistance, for a duration of at least 9 months and longer in immunocompromised patients.…”
Section: Discussionmentioning
confidence: 99%